Diseases of turmeric (Curcuma longa L.) and their management - RAO, T G NAGESHWAR (Journal of Spices and Aromatic Crops, 1995)
Turmeric (Curcuma longa L.) is severely affected by soil borne as well as foliar diseases. Rhizome rot takes a heavy toll in majority of turmeric areas. Among foliar diseases, leaf blotch and leaf spot are important. Several minor diseases have also been reported on the crop. Future studies on crop loss assessment due to these diseases, their epidemiology under .different cropping systems and the role of biocontrol agents and organic amendments in disease suppression need a thorough investigation to develop appropriate disease management strategies. The present status of turmeric diseases and future strategies for their management are outlined in this paper.